Effect of COVID-19 on demand for healthcare in Togo - Yaovi Tossou (Health Economics Review, 2021)
Background: Demand-side barriers to health care are as important as supply-side factors in deterring patients from obtaining effective treatment during COVID-19. Developing countries, including Togo, have focused on reducing the risk of health care utilization during this period by ensuring basic health care services as an important policy to improve health outcomes and meet international obligations to make health services accessible. Methods: The data used to cover all 44 districts in the six (6) health regions of Togo, are from a national home survey. They are collected from July 8th to 17th, 2020. In each district chief town, a minimum of thirty (30) households were included by a systematic two-stage random draw (neighborhood and then home). Based on these data, the multinomial regression model was used to identify risk factors for the request for health care services during COVID-19. Results: A total of 1946 (with a response rate of 98.3%) participants were addressed in the study. The finding on households with age above 60 years indicated that the relative risk ratio (RRR = 23.97; 95% CI = 0.93; 615.38) allowed them to practice self-medication in lieu of modern healthcare facilities. The multinomial model revealed that the relative risk ratio of pre-COVID-19 activities (RRR = 4.87; 95% CI = 1.018; 23.38) permits households to rely on their self-medication choice and (RRR = 3.14; 95% CI = 0.91; 0.83) prefer public health facilities. Given that the head of the households (RRR = 0.19; 95% CI = 0.017, 2.11) is educated, he prefers the choice of private health centers during COVID-19 pandemic to public health facilities. Conclusion: This study has demonstrated that the majority (30.49%) of patients sought health care. The analysis shows that the loss of employment, activities before COVID-19 in households and areas not infected by the pandemics allow them to ask for health care (self-medication and public hospitals) despite the COVID-19 impacts. However, higher education and age determine a different choice of health care delivery by households. Thus, policy makers need to cast special emphasis on social policies to address home health shocks.
Keywords: 330; COVID-19; Pandemics; Health care; Multinomial logit model